Influence of the gut microbiota on the pharmacokinetics of tacrolimus in liver transplant recipients: insights from microbiome analysis - Wang, Yan; Bai, Zhongyuan; Liu, Yufeng; Wang, Yan; Xu, Jun; Lai, Zhiyong (Frontiers in Microbiology, 2025)
IntroductionTacrolimus is crucial for immunosuppression after liver transplantation, but its pharmacokinetics vary markedly among individuals. Emerging evidence suggests that the gut microbiota may influence its metabolism, although the underlying mechanisms remain unclear.MethodsThis study analyzed the fecal microbiota from 38 postliver transplant patients and 31 healthy controls via 16S rDNA amplicon and shotgun metagenomic sequencing. Patients were stratified into three groups on the basis of oral tacrolimus dosage and blood concentration: LDLBC (low dose, low blood concentration), LDHBC (low dose, high blood concentration), and SDLBC (standard dose, low blood concentration).ResultsPosttransplant patients presented significantly reduced gut microbial diversity. Specific bacterial taxa, including Enterococcus raffinosus, Intestinibacter bartlettii, and Bacteroides fragilis, were enriched in patients with lower tacrolimus blood concentrations. In contrast, Phascolarctobacterium faecium and Streptococcus salivarius were associated with increased drug levels. Functional analysis revealed differences between patient subgroups in ATP-binding cassette (ABC) transporters and drug efflux pumps, suggesting a potential microbial influence on tacrolimus absorption and metabolism. Additionally, antibiotic resistance genes were more abundant in patients with lower tacrolimus blood concentrations, particularly in the Escherichia coli-enriched groups.DiscussionThese findings underscore the influence of the gut microbiota on tacrolimus pharmacokinetics and support the potential of microbial composition as a biomarker for optimizing immunosuppressive therapy.